Genetic variability analysis in coriander (Coriandrum sativum Linn.) - S K Singh, S J Singh, (Journal of Spices and Aromatic Crops, 2013)
The investigation was undertaken to assess the genetic parameters in respect of yield and yield determining characters of nine genotypes namely 2007, 8918, 2002, 9903, 9106, 9807, 2015, 2108 (germplasm lines) including check variety Azad Dhania-1 of coriander (Coriandrum sativum). The maximum genotypic coefficient of variability (18.39%), broad sense heritability (93.5%) and genetic advance over mean (36.60%) were obtained for umbels plant-1. Seed yield was positively associated with several characters such as plant height, number of primary branches plant-1, number of secondary branches plant-1, number of umbels plant-1, number of umbellets plant-1, number of seeds umbel-1 and umbel diameters. Quantitative traits like plant height, number of secondary branches plant-1, number of primary branches plant-1, number of umbel plant-1, number of umbellets umbel-1 and number of seeds umbel-1 exhibited wide range of variability, maximum genotypic and phenotypic coefficient of variability, broad sense heritability and genetic gain (as per cent of mean). It was found that the genotypes 9106, 2007, 2108 and 2015 were promising.